OPTIMALISASI KOMUNIKASI TERAPEUTIK CAREGIVER SEBAGAI PENDAMPING PASIEN ODGJ PASCA PENGOBATAN MEDIS - devi nadhifah; Sri Wahyuningsih (Jurnal Spektrum Komunikasi, 2026)
The care of people with mental disorders (ODGJ) after medical treatment requires optimal assistance, especially through therapeutic communication and social support from caregivers. The care process is carried out continuously and requires gradual and consistent handling. This is because ODGJ experience disturbances in their thoughts, feelings, and behavior, which limit their ability to carry out daily activities. This study explores the optimization of therapeutic communication carried out by caregivers as companions to ODGJ patients after medical treatment. The study was conducted using a constructivist paradigm with a qualitative case study approach. Data collection was conducted through in-depth interviews, observations, and documentation using Stake's (1995) data analysis technique through four stages: Categorical Aggregation, Direct Interpretation, Pattern Correspondence, and Natural Generalization, to ensure the consistency of the analysis results, followed by method triangulation, source triangulation, and member checking. The research location was set in Geger Subdistrict, Sabilul Rosyad Campor Foundation area, Bangkalan Regency, considering that this area is one of the subdistricts with a relatively high number of ODGJ, thus indicating a significant need for assistance and sustainable treatment after medical treatment. The study involved seven informants selected using purposive sampling techniques. The results showed that caregivers in Geger Subdistrict had implemented therapeutic communication, although it was still limited to daily interactions without formal training. The dominant optimizing factor was instrumental support, so other optimizing factors were needed to have a greater impact on caregivers in implementing therapeutic communication. The main obstacle was a lack of understanding about continuous care. This study emphasizes the importance of psychoeducation to improve caregivers' communication skills in order to support the recovery of people with mental disorders and prevent relapse.